Pendidikan Islam Multikultural Upaya Menumbuhkan Kesadaran Multikultural - Arifin, Zainal (LPPPM STAI Darul Hikmah Bangkalan, 2018)
Islam moderate, is a typical Indonesian Islam that has been tested by history, and became the inspiration of international Muslims. Islam and Indonesian Muslims continue to find their momentum as a religion that promotes moderate, inclusive, humanist, tolerant and peaceful attitudes, isathiyah Islam is a typical Indonesian Islam. But lately, the uniqueness began to shift. In facts about the conflict and violence perpetrated by individuals and groups in the name of religion even under the pretext of defending religion have undermined diversity and tolerance itself